Health and Wellbeing Spillovers of a Partner's Cancer Diagnosis - Viola Angelini; Joan Costa-Font; Joan Costa-i-Font (Center for Economic Studies and ifo Institute (CESifo), 2023)
Major health shocks can have far-reaching consequences on the welfare of an individual's support and emotional network. This paper investigates both long-term and short-term spillovers of a major non-communicable health shock, namely a cancer diagnosis (CD), on the health and well-being of an individual's partner. We rely on data from a longitudinal sample of individuals over fifty from 19 European countries. Our estimates provide economically relevant evidence of the spillovers of a CD on the partner's mental health and well-being. We document a negative association between a partner's CD and several measures of well-being, which is not driven by changes in health behaviors and persists over time for some dimensions. These findings suggest that focusing on the individual economic impact of a CD is likely to underestimate its long-term welfare effects unless spillovers on the emotional support network are considered.
Keywords: I18; J14; 330; cancer; family spillovers; health behaviors; household well-being; employment; loneliness; welfare effects